Prosecuting a Prophet: Justice, Psychiatry, and Rebellion in Colonial Kenya. (29th December 2020) - MacArthur, Julie
Abstract: In Kenya, the prophecies of the late Elijah Masinde, leader of the anti-colonial religious revival Dini ya Msambwa, remain contested. MacArthur explores the religious innovations, intellectual work, and moral debates for the first time through Masinde's own words. During his 1948 deportation trial, while the prosecution sought to remake Masinde from prophetic madman into calculating criminal, Masinde used the courtroom to challenge the pathologization of rebellion and remake his own patriotic vision. MacArthur argues that Masinde's trial reveals colonial justice and psychiatry as discursive arenas for contestations over resistance, social control, and moral authority in colonial and postcolonial Africa.